2021
DOI: 10.1038/s41598-021-93968-1
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic chemical expansion due to oxygen vacancies in perovskite films

Abstract: In scientifically intriguing and technologically important multifunctional ABO3 perovskite oxides, oxygen vacancies are most common defects. They cause lattice expansion and can alter the key functional properties. Here, it is demonstrated that contrary to weak isotropic expansion in bulk samples, oxygen vacancies produce strong anisotropic strain in epitaxial thin films. This anisotropic chemical strain is explained by preferential orientation of elastic dipoles of the vacancies. Elastic interaction of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The lattice expansion of the Co 3 O 4 -SC catalyst was an important indicator of abundant oxygen vacancies. 21 The existence of oxygen vacancies in the Co 3 O 4 -SC catalyst was further corroborated by the Raman spectra as shown in Fig. 4b.…”
Section: Crystal Structures Of the Catalystssupporting
confidence: 52%
“…The lattice expansion of the Co 3 O 4 -SC catalyst was an important indicator of abundant oxygen vacancies. 21 The existence of oxygen vacancies in the Co 3 O 4 -SC catalyst was further corroborated by the Raman spectra as shown in Fig. 4b.…”
Section: Crystal Structures Of the Catalystssupporting
confidence: 52%
“…170 Computational methods have been actively employed to elucidate the possible magnitude and nature of defect-induced stresses in thin lms and at surfaces. [171][172][173][174][175][176] For example, the recent ab initio calculations showed that tensile or compressive strain stabilizes oxygen vacancies at complex oxide interfaces. 171 This was explained by the chemical expansion due to the defect formation relieving the stress, 172 and is closely related to the anisotropicin directions parallel and normal to the interfacechemical strain observed with in situ TEM, scanning transmission electron microscopy (STEM), electron energy loss spectroscopy (EELS) and optical strain measurements in Ce 1-…”
Section: Atomistic Insightsmentioning
confidence: 99%
“…172,173 The anisotropic character of chemical expansion was also found in perovskitebased epitaxial thin lms using XRD. 174 Both experimental and computational studies 175,176 showed that the nature of the substrate determines the presence of compressive or tensile inplane strain in perovskite La 1-x Sr x CoO 3Àd lms, which impacts the oxygen vacancy concentration therein, inuencing such properties as the oxygen evolution reaction (OER) activity, 175 oxygen surface exchange and diffusion. 176 Due to the promise of higher efficiency of proton-conducting SOFCs, hydration-induced expansion became the focus of multiple studies, including the computational ones.…”
Section: Atomistic Insightsmentioning
confidence: 99%
See 2 more Smart Citations